An Appraisal of Recurrent Miscarriage in Sub-Saharan Africa: Occurrence and Possible Solution - Emiade, Sanmi; Musa, Bolanle OP; Oguntayo, Adekunle O; Hassan, Abduazeez; Balogun, Yemi (Clinical Journal of Obstetrics and Gynecology, 2024)
A recurrent miscarriage may be defined in the African context as the foetal demise of two or more successive pregnancies before the attainment of the age of viability. A literature review was done to assess the trend of recurrent miscarriage in sub-Saharan Africa. Identifying the main causes, considering the population at risk, and the availability of accurate diagnostic utilities to effectively ensure good management of recurrent miscarriage is an important gynaecologic issue. Over the years, studies have identified several etiologies and yet there’s been no tangible implementation of therapeutic strategies. Routine modifications should also be employed to develop new approaches to reproductive prognosis. There is notably scanty information on the cases of spontaneous abortion due to chromosomal abnormalities. Genetic and immunological factors should be considered in the work-up plan for women with RM. About 70% of the cases of RM are considered unexplained, and this may be due to limited resources. We concluded that there is relatively poor management of miscarriage and cases of missed and inaccurate diagnosis of the causes of spontaneous abortion in sub-Saharan Africa. More studies are needed in order to assess the extent of genetic induced miscarriage, where resources are limited, folic acid supplements should be provided for pregnant women.